2019
DOI: 10.32098/mltj.03.2013.16
|View full text |Cite
|
Sign up to set email alerts
|

Suture techniques for tendon repair; a comparative review

Abstract: Over the past five decades we have seen numerous iterations of suture repair methods for tendon. The pursuit of the ultimate repair has led to many repair methods being described. This comprehensive compilation of the suture repair techniques will describe the factors that affect repair success, including repair strength, gapping resistance, glide and rehabilitation. Different approaches to rejoining severed tendons will be critiqued on their biomechanical ability to improve tendon repair strength, maintaining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 92 publications
(57 citation statements)
references
References 41 publications
0
53
0
4
Order By: Relevance
“…The therapy used currently to heal tendon injuries includes surgical suture, transplants such as autograft, allograft, xenograft, and permanent tendon prostheses (Jørgensen, Bak, Ekstrand, & Scavenius, 2001). Suture involves an end-to-end repair to hold the ruptured tendon together (Rawson, Cartmell, & Wong, 2013). However, suture is not applicable for tendon healing with gaps larger than 5 mm (Burkhart, Diaz-Pagàn, Wirth, & Athanasiou, 1997).…”
mentioning
confidence: 99%
“…The therapy used currently to heal tendon injuries includes surgical suture, transplants such as autograft, allograft, xenograft, and permanent tendon prostheses (Jørgensen, Bak, Ekstrand, & Scavenius, 2001). Suture involves an end-to-end repair to hold the ruptured tendon together (Rawson, Cartmell, & Wong, 2013). However, suture is not applicable for tendon healing with gaps larger than 5 mm (Burkhart, Diaz-Pagàn, Wirth, & Athanasiou, 1997).…”
mentioning
confidence: 99%
“…It has been demonstrated that the breaking strength of 2‐0 barbed polypropylene suture is closest to, and not significantly different from, that of smooth 3‐0 polypropylene suture. The barbed suture was also significantly stiffer and had less elongation than any of the smooth suture sizes tested in that study . A recent in vitro veterinary study compared the ultimate tensile strength and load to 1 and 3 mm gap formation between smooth and knotless barbed polypropylene sutures for canine gastrocnemius tendon repair .…”
Section: Discussionmentioning
confidence: 79%
“…The barbed suture was also significantly stiffer and had less elongation than any of the smooth suture sizes tested in that study. 45 A recent in vitro veterinary study compared the ultimate tensile strength and load to 1 and 3 mm gap formation between smooth and knotless barbed polypropylene sutures for canine gastrocnemius tendon repair. 37 Thirty-three paired bone-tendon units were repaired with either 3-0 smooth or 0 knotless barbed polypropylene suture using a three-loop pulley pattern and tested under single-cycle tensile loading until failure occurred.…”
Section: Discussionmentioning
confidence: 99%
“…The prior physiological criteria include, among others, the initial strength recovery, the joint gliding, the re-rupture avoidance and the shorter returntime to activity. Early active mobilization of the repaired tendon is advocated to improve those properties [19]. It was also proved that this early post-surgery stimulation increases the collagen type I cell production and that the quick tension restoration induces the parallel alignment of this renewed collagen [51].…”
Section: Figure 3: Scheme Conciliating Helix Crimp and Linear Organizmentioning
confidence: 99%
“…In the case of small and large rotator cuff tears, surgical repairs of ruptured tendons have re-tear rates of up to 35 and 94%, respectively [18]. Clinicians assess an unsatisfactory clinical outcome after suture for 25% of patients with hand tendon lacerations, and 7.7% of these repairs re-rupture [19].…”
Section: Introduction: Clinical Challengesmentioning
confidence: 99%